Effects of SmartLic Hi-Pro 40 block supplements on ruminal microbes in cattle fed low-quality forages - Derstein, K.D.; Drouillard, James S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2011)
Dormant pastures and native grass hays often are deficient in protein and other nutrients needed to support optimum performance of beef cattle. These nutrients are essential for maintaining viable populations of symbiotic rumen microorganisms that digest the fiber in forages. When nutrient deficiencies occur, microbial populations in the rumen decrease, thereby limiting digestion of low-quality forages. This study was conducted to evaluate changes in rumen microbial populations and digestive activity when cattle consuming low-protein native grass hay are given access to high-protein, free-choice block supplements.
Keywords: Beef; SmartLic Hi-Pro 40; Rumen; Forages; Protein